Threaded Type Integrative Learning Model Develops Creative Thinking Skills of Elementary School Students - Pangestu, Widya Trio; Setyawan, Agung; Maula, Qurrotu (International Journal of Elementary Education, 2023)
Implementing the learning process in several elementary schools still emphasizes mastery of learning materials or theory-based learning. This study aims to analyze the effectiveness of the threaded integrative learning model in developing elementary school students' creative thinking skills as one of the essential skills in the 21st century. This study used an experimental research design with a pretest-posttest control group design. The population of this research is 313 students. The sample of this research was 173 students of class V selected using the cluster random sampling technique. Methods of data collection using tests. The instrument used to collect data is test questions. Data analysis techniques using descriptive qualitative analysis, quantitative, and inferential statistics. The study results showed a difference between the creative thinking skills of the experimental group students, who were taught by the threaded type of integrative learning model, and the control group, who were prepared by conventional methods. The threaded integrative learning model could develop the creative thinking skills of elementary school students. The threaded integrative learning model makes it easier for students to learn so that they can develop the creative thinking skills of elementary school students.